Kewenangan Balai Besar Taman Nasional Kerinci Seblat Dalam Penegakan Hukum Terhadap Perambahan Hutan Di Taman Nasional Kerinci Seblat - Raharja, Ivan Fauzani; Nuriyatman, Eko; Permatasari, Bunga (Jurnal Selat, 2018)
Law the Republic of Indonesia Number 41 of 1999 concerning Forestry defines Forest is a unit of ecosystem in the form of a stretch of land containing biological natural resources dominated by trees in their natural environment, which cannot be separated from one another, in this research researchers conduct research Large Kerinci Seblat National Park (BBTNKS) and at the location of Kerinci Seblat National Park (TNKS), where this study obtained data that in the TNKS area forest encroachment activities are activities for forest clearing with the aim of owning, controlling and utilizing the results forest without seeing and paying attention to the main functions carried out by a forest area. The forest encroachment activities carried out by the community in the TNKS area for agricultural activities which arise due to the need for agricultural land and only a few people in the TNKS area that has their own agricultural land. In this study discussed two things, namely regarding the authority of regional government supervision in overcoming forest encroachment in the TNKS area and the form of forest encroachment control by BBTNKS in the Kerinci National Park area. The research method used in this study is a non doctrinal (empirical) research method to discuss the incompatibility between dasolen and dasein, and to interview several parties that make it possible to provide information related to ongoing research.